2013
DOI: 10.1128/jb.00404-13
|View full text |Cite
|
Sign up to set email alerts
|

Dual Mechanisms of Metabolite Acquisition by the Obligate Intracytosolic Pathogen Rickettsia prowazekii Reveal Novel Aspects of Triose Phosphate Transport

Abstract: Rickettsia prowazekii is an obligate intracytosolic pathogen and the causative agent of epidemic typhus fever in humans. As an evolutionary model of intracellular pathogenesis, rickettsiae are notorious for their use of transport systems that parasitize eukaryotic host cell biochemical pathways. Rickettsial transport systems for substrates found only in eukaryotic cell cytoplasm are uncommon among free-living microorganisms and often possess distinctive mechanisms. We previously reported that R. prowazekii acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Acyl chain incorporation into lipid A follows the structure deduced for R. typhi ( 171 ). While both DHAP and G3P are known to be imported from the host ( 51 , 52 ), Rickettsia species lack enzymes to generate LPA via the first incorporation of hexadecanoyl-ACP (the gray circle represents this pathway hole). All enzymes subsequent to this step are highly conserved (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acyl chain incorporation into lipid A follows the structure deduced for R. typhi ( 171 ). While both DHAP and G3P are known to be imported from the host ( 51 , 52 ), Rickettsia species lack enzymes to generate LPA via the first incorporation of hexadecanoyl-ACP (the gray circle represents this pathway hole). All enzymes subsequent to this step are highly conserved (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenomics studies observed additional depleted metabolic pathways, particularly those for B vitamins, many cofactors, and pentose phosphates ( 48 50 ). Efforts in the postgenomics era identified rickettsial import of the glycerophospholipid precursors dihydroxyacetone phosphate (DHAP) and sn -glycerol 3-phosphate (G3P) ( 51 , 52 ) and also the cosubstrate S -adenosylmethionine (SAM), for which a novel transporter (EamA) was characterized ( 53 ). Additionally, substrate ranges of four Tlc1 paralogs (Tlc2 to Tlc5) were investigated, revealing that none function in energy exchange, yet two import host ribonucleotides (Tlc4 [CTP, UTP, and GDP] and Tlc5 [GTP and GDP]) ( 54 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, strain w DacB possessed three uptake systems of the drug/metabolite transporter (DMT) superfamily, and two genes for organophosphate:phosphate MFS antiporters that were not present in w DacA. The former DMT transporters were > 75% similar to the S-adenosylmethionine (SAM) uptake transporter of Rickettsia prowazekii ( Tucker et al 2003 ), and the highest similarities (∼49%) of the latter MFS antiporters were to proteins of R. prowazekii which have been implicated in triose phosphate uptake used for phospholipid biosynthesis ( Frohlich and Audia 2013 ). No hexose transporter genes were found, supporting the theory that there is no glycolysis in both strains.…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian Host Cells during Infection ("Pathometabolism") existing rickettsial triose phosphate transport systems (108). The existence of a large number of transporters for catabolic intermediates and anabolic monomers is indeed a hallmark of R. rickettsiae (105,(109)(110)(111)(112).…”
Section: Metabolic Adaptations Of Intracellullar Bacterial Pathogensmentioning
confidence: 99%
“…The hitherto poorly understood regulation of the rickettsial metabolite transporters in the course of the host cell infection is probably decisive for the balanced interaction of the host and the parasite since both partners compete, more or less, for the same nutrient pool. In this context, it has been proposed that the rickettsial transport systems might even be considered as metabolic virulence factors (108).…”
Section: Metabolic Adaptations Of Intracellullar Bacterial Pathogensmentioning
confidence: 99%